Walsh, Daphne. New Perlican Photograph of a man on the water. - Barrett, Terra (1945)
A photograph of William Hobbs on the water at The Big Pond in New Perlican, approximately 1945. Above the photo says "Family Memories" and below the photo says "Dad." The photograph was printed by Kodak.